Spiritual Experience Among Cervical Cancer Survivors: A Phenomenology Study - Hernandia Distinarista (NURSCOPE: Jurnal Penelitian dan Pemikiran Ilmiah Keperawatan, 2018)
Spirituality is needed in dealing with cervical cancer patients. Researches show that cervical cancer patients who have low spiritual level tend to be more depressive compared to those with good spiritual level. This study aimed to explore the spiritual experience of survivor among cervical cancer patients. The study used a hermeneutic phenomenology method, involving five participants in Demak, Jepara and Kendal areas. Data retrieval was collected by semi structured interview followed by data transciption. Data analysis used content analysis. The finding showed that the spiritual gave strength and motivation to those participants since they were having treatment until healed.